Status Kognitif dan Kualitas Hidup Lansia - I Wayan Suardana; Luh Gede Intan Saraswati; Ria Fitriani (Jurnal Gema Keperawatan, 2015)
The purpose of this research was to know correlation between cognitive status and quality of life of the elderly in the village of Sanding work area clinics I Tampaksiring. This observation is a descriptive by used cross-sectional sample of 67 respondents were taken by used a purposive sampling technique. Indicated showed the cognitive status of elderly most 21,99 in category light. Quality of life of the elderly is largely 77,76 in the category quite nicely. Based on the correlation with product moment p value of 0.000 ( p = 0.05), indicating no relationship between cognitive status and quality of life of the elderly. The value of the correlation coefficient of 0,549 constitute a relationship variables have a degree of relationship that is a positive direction and the relationship between the variables.